High proportion of depression and anxiety in younger patients with COPD: a cross-sectional study in primary care in Sweden - Therese Öfverholm; Mikael Hasselgren; Karin Lisspers; Anna Nager; Gabriella Eliason; Maaike Giezeman; Christer Janson; Marta A. Kisiel; Scott Montgomery; Björn Ställberg; Josefin Sundh; Hanna Sandelowsky (Scandinavian Journal of Primary Health Care)
Background and aim Patients with COPD and concurrent depression and/or anxiety are known to have an increased risk of exacerbations, morbidity, mortality, and deteriorated quality of life. Early detection of depression/anxiety may enable early interventions. The aims of this study were to describe the occurrence of depression and anxiety in primary care patients with COPD in Sweden, and to investigate age and gender differences together with other clinical factors associated with this comorbidity.Methods A cross-sectional study was performed on a cohort of patients with doctor’s diagnoses of COPD. Patients were randomly selected based on the patients’ contact with 98 primary healthcare centers and 13 hospitals in Sweden in 2014. Information about self-reported depression/anxiety, patient characteristics, symptoms, and comorbidity, were collected using patient self-completion questionnaires. Lung function data were extracted from medical records.Results Of the 2245 patients recruited, 23% (n = 524) reported depression/anxiety, 29% in women and 16% in men (p <0.001). Factors associated with depression/anxiety were being a woman (OR = 2.06 [95% CI 1.56–2.72]), current smoking (1.83 [1.37–2.43]), comorbid asthma (1.77 [1.32–2.37]), dyspnea (the modified Medical Research Council dyspnea scale ≥2 points) (1.58 [1.17–2.13]) and age <65 years (1.57 [1.17–2.10]). The youngest age groups had the highest proportions of patients with depression/anxiety.Conclusions Healthcare professionals need to be particularly aware of depression/anxiety in patients with COPD who are younger, women, current smokers, have comorbid asthma, or dyspnea.